A Comparison of the Neurospora and Drosophila Clocks. Issue 2 (April 2020) - Brody, Stuart
In Neurospora and other fungi, the protein frequency (FRQ) is an integral part and a negative element in the fungal circadian oscillator. In Drosophila and many other higher organisms, the protein period (PER) is an integral part and a negative element of their circadian oscillator. Employing bioinformatic techniques, such as BLAST, CLUSTAL, and MEME (Multiple Em for Motif Elicitation), 11 regions (sequences) of potential similarity were found between the fungal FRQ and the Drosophila PER. Many of these FRQ regions are conserved in many fungal FRQ(s). Many of these PER regions are conserved in many insects. In addition, these regions are also of biological significance since mutations in these regions lead to changes in the circadian clock of Neurospora and Drosophila . Many of these regions of similarity between FRQ and PER are also conserved between the Drosophila PER and the mouse PER (mPER2). This suggests conserved and important regions for all 3 proteins and a common ancestor, possibly in those amoeba, such as Capsaspora, that sits at the base of the phylogenetic tree where fungi and animals diverged. Two additional examples of a possible common ancestor between Neurospora and Drosophila were found. One, the white collar (WC-1) protein of Neurospora and the Drosophila PER, shows significant similarity in its Per/Arnt/Sim (PAS) motifs to the PAS motif of an ARNT-like protein found in the amoeba, Capsaspora . Two, both of the positive elements in each system (i.e., WC-1 in Neurospora and cycle [CYC] in Drosophila ), show significant similarity to this Capsaspora ARNT protein. A discussion of these findings centers on the long-time debate about the origins of the many different clock systems (i.e., independent evolution or common ancestor as well as to the question of how new genes are formed).